Beginning Ubuntu LTS Server Administration 2nd Edition - Vugt, Sander van (Apress, 2012)
Beginning Ubuntu LTS Server Administration: From Novice to Professional, Second Edition provides a complete introduction to Ubuntu Server. I wrote it for people who are new to Ubuntu Server administration but have a solid foundation in IT. The target readers are Windows administrators as well as people who are used to managing other flavors of Linux (or UNIX). It was the goal of this book to give a no-nonsense introduction to working with Ubuntu Server, so it provides all the basics that are needed to get you going. It also includes many useful tips that help you do your work in a more efficient manner. Many books about Ubuntu are presently available, but you can’t do Ubuntu Server justice by covering both the desktop and the server version in one book. The needs of a server administrator are vastly different from the needs of a desktop administrator. So I chose an approach that makes sense for the server administrator, and all topics are selected and organized to make sense for your day-to-day work as a server administrator.